Growth analysis of six lisianthus (Eustoma grandiflorum) cultivars in different growing seasons - Höhn, Daniela; Peil, Roberta Marins Nogueira; Marchi, Priscila Monalisa; Trentin, Roberto; Grolli, Paulo Roberto (Comunicata Scientiae, 2024)
The objective of work was to evaluate the growth of six lisianthus cultivars at different times, in a protected environment, in the southern region of Brazil. The experimental design was randomized blocks, in split plots, with three replications. The plots were constituted by the lisianthus cultivars: 'White Excalibur', 'Blue Picotee', 'Blue Echo', 'Arena Red', 'Robella' and 'Echo Champagne'and the subplots by the dates of plant collections (evaluations), which were carried out at the time of transplantation (0) and 21, 42, 63 and 84 days after transplantation (DAT) for seasons 1(October 2017 to January 2018), 2 (November 2017 to February 2018) and 5 (August to December 2018); and at (0) and at 30, 60, 90, 120, 150 and 180 DAT at seasons 3 (April to November 2018), 4 (July to December 2018) and 6 (February to June 2019). All cultivars showed an increasing tendency to accumulate a dry mass of the plants until the harvest of the floral stems. The maximum dry mass value was obtained by the cultivar 'Robella' (20.3 g/plant-1) in season 3. For all cultivars, the absolute and relative growth rates of the crop increased with the advancement of the cultivation period. In seasons 1, 2 and 5 all cultivars showed higher growth velocities between 63 and 84 days after transplanting (DAT). In seasons 3 and 4 the cultivars showed higher growth from 90 to 150 DAT. In seasons 1 and 2 the cultivars showed a higher rate of plant growth, resulting in a shortening of the cycle. The cultivars conducted in seasons 3 and 4 had a longer cultivation time due to the autumn/winter period. The cultivar 'Arena Red' showed the lowest growth rates in all seasons.